Primary Health Care Characteristics: A view from Family Medicine Standpoint - Rosas Prieto, Alex Moisés (2013)
In this article we invite our readers to know about primary care,their differences with the secondary care and its importance in the current health systems. We talk about the four attributes of primary care described by Barbara Starfield : Accessibility and first contact where there should be easy access to the health system; Longitudinality, which must establish a personal relationship between the physician and continuous patient .Integrity,which gives solution to the most common health needsof the community and Coordination, where there isa joint effort between primary care physicians and other specialists.